Measurements of charged current lepton universality and |Vus| using tau lepton decays to e−ν[bar]eντ, μ−ν[bar]μντ, π−ντ, and K−ντ - Aubert, Bernard; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review letters, 2010)
Using 467 fb−1 of e+e− annihilation data collected with the BABAR detector, we measure B(τ−→μ−¯νμντ)B(τ−→e−¯νeντ)=(0.9796±0.0016±0.0036), B(τ−→π−ντ)B(τ−→e−¯νeντ)=(0.5945±0.0014±0.0061), and B(τ−→K−ντ)B(τ−→e−¯νeντ)=(0.03882±0.00032±0.00057), where the uncertainties are statistical and systematic, respectively. From these precision τ measurements, we test the standard model assumption of μ−e and τ−μ charge current lepton universality and provide determinations of |Vus| experimentally independent of the decay of a kaon.
*BABAR Collaboration: B. Aubert, J. Marks, S. Schenk, U. Uwer [und 489 weitere Personen]
Im Titel steht der erste und der dritte Buchstabe v mit einem Oberstrich
Im Titel ist der Ausdruck "us" tiefgestellt
Im Titel ist das Minuszeichen hochgestellt
Im Titel ist der Buchstabe "tau" im Bereich der Formeln tiefgestellt